HUBUNGAN MUTU PELAYANAN PERAWAT TERHADAP KEPUASAAN PASIEN RAWAT INAP DI RUMAH SAKIT PABATU PTPN IV TAHUN 2017 - TRI ANGGUN APRIANI (LP2MTBM MAKARIOZ, 2018)
Nursing is often referred to as the spearhead of services in hospitals. The high demand of the community for nursing services and the emergence of competition in many sectors requires nurses to be able to compete by providing quality services, especially nursing services carried out in the inpatient room. The number of nurses is the most energy when compared to other health workers, so its role becomes a determinant in health services in hospitals. In addition, nurses interact with patients for 24 hours to carry out nursing services (Nursalam, 2015).Patient satisfaction is the level at which someone states the results of the comparison of the performance of products and services received with the expected. Patient satisfaction is one of the important indicators that must be considered in health services. Patient satisfaction is the result of assessment of patients on health services by comparing what is expected in accordance with the reality of health services received in a hospital health setting (Kotler, 2012). Thus patient satisfaction at the hospital depends on how the services provided by the hospital.